Metastatic hepatocellular carcinoma in the maxilla and temporal bone: a rare case report - Cho, Juyeon (J Korean Assoc Oral Maxillofac Surg, 2021)
Hepatocellular carcinoma (HCC) is a common, primary malignant liver disease that usually metastasizes to the lungs, followed by the abdominal lymph nodes and brain. However, extrahepatic metastasis to the maxillofacial area is uncommon and predominates in the mandible, so HCCs in the maxilla or temporal bone from a primary hepatic lesion are extremely rare. We present a case of HCC in the maxilla and temporal bone in a 52-year-old male, which was first suspected to be a squamous cell carcinoma after computed tomography but was confirmed as a metastasis related to his primary HCC after fine-needle aspiration biopsy followed by immunohistochemical analysis.